Africa needs context-relevant evidence to shape its clean energy future - Mulugetta, Y; Sokona, Y; Trotter, PA; Fankhauser, S; Omukuti, J; Somavilla Croxatto, L; Steffen, B; Tesfamichael, M; Abraham, E; Adam, J-P; Agbemabiese, L; Agutu, C; et al. (Springer Nature, 2022)
Aligning development and climate goals means Africa’s energy systems will be based on clean energy technologies in the long term, but pathways to get there are uncertain and variable across countries. Although current debates about natural gas and renewables in Africa are heated, they largely ignore the substantial context specificity of the starting points, development objectives and uncertainties of each African country’s energy system trajectory. Here we—an interdisciplinary and majority African group of authors—highlight that each country faces a distinct solution space and set of uncertainties for using renewables or fossil fuels to meet its development objectives. For example, Ethiopia is headed for an accelerated green-growth pathway, but Mozambique is at a crossroads of natural gas expansion with implicit large-scale technological, economic, financial and social risks and uncertainties. We provide geopolitical, policy, finance and research recommendations to create firm country-specific evidence to identify adequate energy system pathways for development and to enable their implementation.